Glucocorticoids inhibit neurogenic plasma extravasation and prevent virus-potentiated extravasation in the rat trachea. - Piedimonte, G (1990)
Capsaicin increases the permeability of blood vessels in the rat tracheal mucosa through a mechanism involving the release of tachykinins from sensory nerves. This capsaicin-induced increase in vascular permeability is potentiated by viral infections of the respiratory tract. The present study was done to determine whether this "neurogenic plasma extravasation" can be inhibited by glucocorticoids, to learn the time course of this inhibition, and to determine whether glucocorticoids can prevent the potentiating effect of viral respiratory infections on neurogenic plasma extravasation. Groups of pathogen-free F344 rats were treated with dexamethasone for 2 or 8 h (4 mg/kg i.p.) or 48 or 120 h (0.5-4 mg/kg per d i.p.). Another group of rats was treated with dexamethasone for 120 h following the intranasal inoculation of Sendai virus. The magnitude of plasma extravasation produced by capsaicin or substance P was assessed after this treatment by using Monastral blue pigment and Evans blue dye as intravascular tracers. We found that dexamethasone reduced, in a dose-dependent fashion, the magnitude of plasma extravasation produced in the rat trachea by capsaicin and substance P. Significant inhibition was produced by a dose of dexamethasone as small as 0.5 mg/kg i.p. The effect of dexamethasone had a latency of several hours and reached a maximum after 2 d of treatment. Furthermore, dexamethasone prevented the potentiation of neurogenic plasma extravasation usually present after 5 d of Sendai virus respiratory infection.